2017
DOI: 10.1007/s13197-017-2544-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenolic profile and antioxidant capacity of different fruit part from lemon (Citrus limon Burm.) cultivars

Abstract: Phenolic composition and antioxidant capacity of different fruit part including peel, pulp, juice, whole fruit and seed from five lemon cultivars (Feiminailao, Cuningmeng Limeng, Pangdelusaningmeng, Beijingningmeng) were investigated. Caffeic acid (9.31-741.4 lg/g FW) and chlorogenic acid (2.7-527.5 lg/g FW) were the dominant phenolic acid in fruit tested, Pangdelusaningmeng (PD) and Limeng peels with the highest contents, respectively. Hesperidin was the predominant flavanone (10.27-3315 lg/g FW), Cuningmeng … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
67
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 32 publications
22
67
2
5
Order By: Relevance
“…Lemon fruit is rich in antioxidant compounds with health beneficial effects, with one of the most important groups being phenolic compounds, although their profile and concentration depends on environmental conditions for growth, as well as the cultivar and fruit part . The results of the present study show that the phenolic concentration was higher in flavedo than in juice in both cultivars ‘Fino’ and ‘Verna’, although the phenolic concentration in juice was higher in ‘Fino’ than in the ‘Verna’ cultivar, whereas, in flavedo, the highest phenolic content was found in ‘Verna’.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Lemon fruit is rich in antioxidant compounds with health beneficial effects, with one of the most important groups being phenolic compounds, although their profile and concentration depends on environmental conditions for growth, as well as the cultivar and fruit part . The results of the present study show that the phenolic concentration was higher in flavedo than in juice in both cultivars ‘Fino’ and ‘Verna’, although the phenolic concentration in juice was higher in ‘Fino’ than in the ‘Verna’ cultivar, whereas, in flavedo, the highest phenolic content was found in ‘Verna’.…”
Section: Discussioncontrasting
confidence: 42%
“…Lemon fruit is rich in antioxidant compounds with health beneficial effects, with one of the most important groups being phenolic compounds, although their profile and concentration depends on environmental conditions for growth, as well as the cultivar and fruit part. 19,29,30 The results of the present study show that the phenolic concentration was higher in flavedo than in juice in both cultivars 'Fino' and 'Verna', although the phenolic concentration in juice was higher in 'Fino' than in the 'Verna' cultivar, whereas, in flavedo, the highest phenolic content was found in 'Verna'. However, in both cultivars, MeJA treatment increased significantly total phenolic concentration in flavedo and juice and the most effective dose was 0.1 mmol L -1 , with increases of 65% and 39%, respectively, in 'Fino' and 36% and 10%, respectively, in 'Verna' (Tables 1 and 4).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Nectarines are a good source of natural antioxidants, which provide protection against harmful reactive oxygen species and are associated with a lower incidence of chronic diseases (Shui&Leong 2006). The antioxidant contents showed an initial increase, followed by a decrease during cold storage ( Figure 8); this is consistent with previous studies (Xi et al 2017;Zhao et al 2018). The results of antioxidant activity showed that fruits treated with SA and UT and combination of SA and UT had higher antioxidant activity than control fruits after 60 days of storage.…”
Section: Antioxidant Contentsupporting
confidence: 91%
“…Total flavonoid content (TFC) was determined using the sodium nitrite aluminum nitrate colorimetric method as outlined by Xi and Lu. [32] The 200 μL sample solution was mixed with 60 μL sodium nitrite (NaNO 2 , 5 % w/v) for 6 min, then 60 μL of aluminum nitrate (Al (NO 3 ) 3 , 10 % w/v) was added and left to react for 6 min. Then 800 μL of 1 M NaOH solution was added and left to react for 15 min.…”
Section: Determination Of Total Flavonoid Contentmentioning
confidence: 99%